Cover system for roofs manufactured with recycled polyethylene and rubber - Gaggino, Rosana (2015)
The intense waste generation moved by the urban and industrial activity and the wasteful consumption of natural resources, encourage the development of new technologies for the utilization of wastes and its reuse in new industrial processes, which decreases the environmental pollution and the removal of virgin materials. In this sense we work in the development of new materials and components from urban and industrial waste prepared by different techniques and with various applications. We work on the development of a composite material made with recycled rubber from tires out of use (NFU) and recycled polyethylene, linked through the fusion of the plastic and the subsequent pressing of the material. In this article we present the partial results obtained in the physical and mechanical testing of the roof tiles, and the burning behavior of the components manufactured with flame retardants additives available in the market, to comply with the regulations in order to use these housing components. These components have as main advantages the high resistance to flexion and the hard impact, low thermal conductivity, and low water absorption by immersion in water. Despite the fact that the components do not meet all the points of the reference Norm in regard to its behavior when exposed to fire, further amendments in the formulation and the manufacture process have shown interesting results, with which roof tiles could comply with the regulation for the use proposed. We developed a sustainable covering system for roof using two types of wastes in great abundance in all urban sites, which involve a simple manufacture process. Besides, due to its high flexibility and resistance to impact hard is presented as a good constructive alternative for housing covering in areas affected by the fall of hail or by the risk of blowing up and deterioration by strong winds.